Laparoscopie collection and transfer of Chios sheep embryos - AMIRIDIS (Γ.Σ. ΑΜΟΙΡΙΔΗΣ), G. S.; KUEHHOLZER, B.; BESENFELDER, U.; LYMBEROPOULOS (Α. ΛΥΜΠΕΡΟΠΟΥΛΟΣ), A.; VAINAS (Ε. ΒΑΪΝΑΣ), E. (Journal of the Hellenic Veterinary Medical Society, 2018)
The efficiency of two different laparoscopic techniques for embryo collection was examined. Two groups (A and B) of 12 Chios breed ewes were used as donors and 20 crossbred Chios ewes as recipients. Oestrus was synchronised by intravaginal sponges, the donors were supervoulated by 8,8 mg of ovine FSH and laparoscopic intrauterine artificial insemination was conducted with extended fresh ram semen. Embryo collection was carried out the 6th day after AI. The uteri of the animals of group A were flushed after catheterisation of the ipsilateral oviduct. In the animals of group Β a flushing catheter was inserted close to the tip of the horn. Fifty nine and 46 embryos were collected from groups A and Β corresponding to recovery rate of 51.75% and 39% respectively (P>0.05). Laparoscopic transfer of 43 fresh embryos resulted to 11 (55%) pregnancies with (39.5%) surviving fetuses.